Bem de família e mínimo existencial - Gouvêa, Eduardo Mingorance de Freitas (2019)
This dissertation aims to study the possibility of the homestead exemption institute be subjected to weighting, as far as unseizability is concerned, due to a certain assumption. After introducing the main topic, family law and the current forms of families will be discussed, followed by the protection that the State places in that institute. Homestead exemption is investigated along its history showing its development in foreign and homeland law and seeking to comprehend the basis for its existence in face of society practices. The study also examines how the legal rules of this institute are defined in the Brazilian legal order and how the courts apply them. The existential minimum is examined to understand how a right can be categorized as such, to learn its concepts, and the advantages of it being part of this institute. Thereafter, it is investigated whether homestead exemption falls within that approach and if there would be a possibility for its complete non-application. The possibility of homestead exemption having its content mitigated by Robert Alexy’s balancing technique or Humberto Ávila's postulates is examined. Furthermore, the ways of interpreting the legal norm applied to the homestead exemption are identified in order to draw a conclusion on how the courts enforce that institute today as well as to provide insights for understanding the techniques adopted. Finally, rules that should be subject to a legislative update are proposed in order to adapt the norm to the country’s current reality. Moreover, the US institute of homestead exemption is appointed as an idea to have a more updated norm that would cause less injustice